Poly(carboxyethyl acrylate‐co‐ethylene glycol dimethacrylate) precursor monolith with bonded octadecyl ligands for use in reversed‐phase capillary electrochromatography. Issue 24 (7th August 2021) - Neequaye, Theophilus; El Rassi, Ziad
Abstract: A carboxy precursor monolithic column, namely poly(carboxy ethyl acrylate‐co‐ethylene glycol dimethacrylate) was first produced in a 100 μm i.d. fused‐silica capillary and subsequently surface bonded with n ‐octadecyl (C18 ) ligands by a post‐polymerization functionalization process with octadecylamine in the presence of N, N´ ‐dicyclohexylcarbodiimide. The bonding of octadecyl ligands was achieved via an amide linkage between the carboxy functions of the precursor monolith and the amino group of the octadecylamine compound. The resulting C18 monolith exhibited a very low electroosmotic flow (EOF), a fact that required the incorporation of small amounts of 2‐acrylamido‐2‐methylpropane sulfonic acid (AMPS) in the polymerization solution to produce a precursor monolith with fixed negative charges of sulfonate groups. This may indicate that the conjugation of the carboxy functions with octadecylamine occurred to a large extent so that the amount of residual carboxy functions was sparsely dispersed and not enough to produce a desirable EOF. The EOF velocity of the C18 column having fixed negative charges provided by the incorporated AMPS increased with increasing ACN content of the mobile phase signaling an increased binding of mobile phase ions to the polar amide linkages near the monolithic surface, and a decreased viscosity of the mobile phase, both of which would result in increased EOF velocity. The C18 monolithic column constituted a novel nonpolar sorbent for reversed‐phase capillary electrochromatography for nonpolar solutes, e.g., alkylbenzenes, alkylphenyl ketones, and polyaromatic hydrocarbons, and slightly polar compounds including phenol and chlorophenols. The C18 monolithic column exhibited relatively high selectivity toward chlorophenols differing by one chloro substituent.